Características do fresamento assimétrico do aço AISI 4340 endurecido com ferramentas de metal duro recobertas com TiAIN e TiN - Souza, Marcelo Capello Rolim de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
New methods have been studied to optimize machining processes, aiming at reducing costs and consequently increasing productivity, leading to a decrease in the possible environmental impacts that were related to these processes. Among the several methods currently under consideration, the most important ones today are those related to dry machining along with the machining of hardened steels, which has resulted in an evolution in the tools used, which each time have more sophisticated coatings. These improvements aim to eliminate the rectification steps that make the whole process more expensive. Based on the above, this work has as main objective to evaluate the asymmetric milling in different conditions analyzing the output variables: surface quality, power consumed, vibration, acoustic emission, tool wear and chip. This work analyzed the machining process of hardened AISI 4340 steel through asymmetric front milling in two different conditions, in one of which the machining width condition was less than half the diameter of the milling cutter and in the other condition of machining width was greater than half the milling cutter diameter. The influence of cutting speed and feed rate was also analyzed. Hard metal tools with TiAlN and TiN coating were used and no type of lubrication was used. A complete factorial type experiment design with two cutting widths was adopted, being 1/3 and 2/3 of the cutter diameter, 3 cutting speeds (150, 200 and 250 m/min) and two advances (0.1 and 0.2 mm/rot). To analyze the results, analysis of variance (ANOVA), Tukey's test, regression analysis and desirability analysis were used. For the first condition of asymmetry, in which the machining width is less than half the diameter, it was observed that the highest average roughness value Ra was obtained for the cutting speed Vc = 200 m/min, showed ...(Complete abstract click electronic access below)

Novos métodos vem sendo estudados para otimizar os processos de usinagem, visando a redução de custos e seu consequente aumento de produtividade, ocasionando a diminuição dos possíveis impactos ambientais, que eram relacionados a estes processos. Dentre os diversos métodos em destaque, hoje, os que possuem maior importância, são àqueles relacionados a usinagem a seco juntamente com a usinagem de aços endurecidos, o que ocasionou uma evolução nas ferramentas utilizadas, que cada vez possuem recobrimentos mais sofisticados. Estas melhorias visam eliminar as etapas de retificação que encarecem todo o processo. Com base no exposto, este trabalho tem como objetivo principal avaliar o fresamento assimétrico em diferentes condições analisando as variáveis de saída: qualidade superficial, potência consumida, vibração, emissão acústica, desgaste da ferramenta e cavaco. Este trabalho analisou o processo de usinagem do aço AISI 4340 endurecido, através do fresamento frontal assimétrico em duas diferentes condições, sendo que em uma delas a condição de largura de usinagem utilizada foi menor que a metade do diâmetro da fresa e na outra, a condição de largura de usinagem foi maior que metade do diâmetro da fresa. Analisou-se ainda a influência da velocidade de corte e do avanço. Foram utilizadas ferramentas de metal duro com recobrimento de TiAlN e TiN e não foi utilizada nenhum tipo de lubri-refrigeração. Foi adotado um planejamento de experimentos do tipo fatorial completo com duas larguras de corte, sendo 1/3 e 2/3 do diâmetro da fresa, 3 velocidades de corte (150, 200 e 250 m/min) e dois avanços (0,1 e 0,2 mm/rot). Para tratar os resultados, foram utilizadas análises de variância (ANOVA), teste de Tukey, análise de regressão e análise de desejabilidade. Para a primeira condição de assimetria, ...(Resumo completo, clicar acesso eletrônico abaixo)
Characteristics of asymmetric milling of hardened AISI 4340 steel with TiAIN and TiN coated carbide tools
Keywords: Usinagem; Aço; Aspereza de superfície; Machining